Performance Analysis of DE-QPSK with Joint Transmit and Receive Diversity in Nakagami Fading - Guangqiu Li; Jiayun Dong (Dianxin kexue)
By using the statistical average results of higher-order powers of Gaussian Q-function in multi-branch diversity reception with maximum ratio combining（MRC）in Rayleigh fading channel，exact closed-form for the average symbol error rate（ASER）of differentially encoded quadri-phase shift keying（DE-QPSK）using coherent detection with transmit selection combining（SC）and receive MRC（SC/MRC）in Nakagami fading channels was derived.Approximate closed-form for the ASER of DE-QPSK with SC/MRC in Nakagami fading channels was derived by using the approximate expression of Gaussian Q-function and moment generating function based analysis approach.Numerical and simulation results show that the theoretical analysis of the ASER of DE-QPSK is exact and the approximate closed-form for the ASER of DE-QPSK is accurate.The above results can be used to design SC/MRC antenna diversity systems with DE-QPSK.